MODERN REVIEW OF ISLAMIC COMMUNICATION MARKETING - Moch Shohib; M. Saiful Hasan; M. Abdul Halim Sidiq (Institut Pesantren KH Abdul Chalim Mojokerto, 2022)
Modern communication is not something that is foreign in the era of globalization, the internet and technological developments have opened the potential of two-way marketing communication, namely online and offline communication is needed for companies. Modern communication can be a company opportunity or even a challenge for companies in marketing their products. A case study using the mix method method the researcher uses to reveal the marketing implementation of PT. X in the field taken from interview data sources, observations, documentation and questionnaires. The results showed that PT. X applies modern communication in promoting products through online communication by utilizing social media such as WhatsApp, Facebook, Tiktok, Instagram, Snack Video, Hello, Youtube and the website of PT. X, while the offline communication of PT. X applies direct communication served at the marketing office and indirect communication in introducing their products through a sharing program to be distributed to mosques, prayer rooms and the poor. Modern communication applied by PT. X has the principle of Islamic communication and raises aspirations and results towards marketing and the company's brand image